The Effectiveness of National Collective Management Organization Regulation - Sardjono, Agus; Prastyo, Brian Amy; Larasati, Derezka G. (Indonesia Law Review, 2016)
Law Number 28 of 2014 concerning Copyright in Article 89 provides for two National Collective Management Organizations (briefly referred to as LMKN), both of which represent the interests of Authors and the Owners of Related Rights. Both of the said organizations possess the authority to impose, collect, and distribute royalty obtained from commercial users. The Minister of Law and Human Rights inaugurated commissioners assigned to the said Authors’ LMKN and Related Rights LMKN. The LMKN is bound to have an operational effect on previously existing LMKs in Indonesia. Therefore, the objective of this study is to assess whether the existing LMKs feel that their needs are accommodated by the introduction of the LMKN. This research also aims to reveal the causing factors of the conflict which has been occurring between LMK and Authors/ Musicians/Singers, between LMKs, and between LMK and Commercial Users of Songs/Music. This research also aims to elaborate on the existing regulation patterns concerning LMKs worldwide. The research will be conducted by using the normative and empirical legal research method. Normative research will be conducted to examine the normative aspects of LMK and LMKN. On the other hand, empirical research will be aimed at understanding and analyzing the outlook of actors, particularly LMKs existing prior to the 2014 Copyright Law coming into effect. This research is expected to come up with recommendations concerning the regulation of music/song LMKs in Indonesia in the future.